Perbandingan Harga Pokok Kopi Arabika Dan Kopi Robusta Dari Sisi Proses Pengolahan Kopi: Studi Kasus PTPN XII Kalisat Jampit Bondowoso dan Perkebunan Rakyat Andungbiru Tiris Probolinggo - Yunda Ratih Ratindra; R. Hery Koeshardjono; Judi Suharsono (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2019)
Coffee constitute on of the commodity mainstay plantage be the that possess contribution a big enough in economy Indonesia. Coffee arabica and coffee robusta constitute coffee drink the very by the people of fond. Purpose of research this be for know result for difference process a processing coffee arabica and coffee robusta, for know and acquire result comparison price basic production in coffee arabica and coffee robusta for side process a processing coffee with method full costing and variabel costing. Population which in take of whole price basic production as long as one time harvest in a one year, whereas sample which in take of price basic production in a whole manner of population, because researcher take 100 day picking in a one year very as long as three month production. Research this use research quantitative, purpose research quantitative depict data research of numbers. Result a research that indicate, process a processing coffee arabica which in did by PT. Perkebunan Nusantara XII use manner wet and Perkebunan Rakyat use process a processing coffee robusta with manner dry. For computation price basic production follow method full costing coffee arabica as big as Rp 1.027.641.350 and coffee robusta as big as Rp 339.059.600, whereas follow method variabel costing coffee arabica as big as Rp 975.441.500 and coffee robusta as big as Rp 316.646.000.